Impact of Rho-Kinase Inhibitor Hydroxyfasudil in Protamine Sulphate Induced Cystitis Rat Bladder - AKIN, Yigit; BOZKURT, Aliseydi; EROL, Huseyin S.; HALICI, Mesut; CELEBI, Fikret; KAPAKIN, Kubra A. T.; GULMEZ, Hakan; ATES, Mutlu; COBAN, Abdulkadir; NUHOGLU, Baris (Lower urinary tract symptoms, 2015)
Objectives The objective of the present study was to evaluate anti‐inflammatory effects of hydroxyfasudil in a protamine sulfate (PS) induced cystitis rat model. Additionally, we investigated prevention of bladder overactivity (BO), and tissue damage in these experiments. Methods Animals were divided into four groups. In Groups 1 and 2, chemical induced cystitis model was created by administrating intravesical PS with PE50 catheter by the transurethral route. In Group 1, Rho‐kinase inhibitor hydroxyfasudil was administered intaperitoneally, and in Group 2, subjects were administered a corresponding volume of saline in the same way. In Group 3, vehicle was administered intravesically and hydroxyfasudil was administrated intraperitoneally. Group 4 was a control Group, and the vehicle was administered intravesically and intraperitoneally. Micturition frequencies were recorded. Biochemical analyses were performed for oxidative stress, and pathological evaluations were investigated. In vitro contractions of bladder tissue strips were measured in tissue‐bath. Results There were significantly lower Lipid peroxidase levels and higher levels of Glutathione in Group 1 than Group 2 (P = 0.016, P = 0.001, respectively). There was generally more inflammation in Group 2 than the other groups as determined by microscopy. There were significantly higher frequencies of micturition, lower volume, and mean voided maximum urine output after PS administration in Groups 1 and 2. In vitro contraction responses of bladder strips to potassium chloride and acetylcholine were statistically higher in Group 2 than Groups 1 and 3. Conclusions Significant reduction of inflammation by affecting the anti‐oxidant defense systems was provided by hydroxyfasudil. Decreased in vitro responses to contractions of bladder smooth muscle strips were obtained. Hydroxyfasudil may be a potential new therapeutic option for inflammation and BO, in rat bladder.